Polarisation-controlled single photon emission at high temperatures from InGaN quantum dots - Wang, T; Puchtler, T; Zhu, T; Jarman, J; Nuttall, L; Oliver, R; Taylor, R (Royal Society of Chemistry, 2017)
Solid-state single photon sources with polarisation control operating beyond the Peltier cooling barrier of 200 K are desirable for a variety of applications in quantum technology. Using a non-polar InGaN system, we report the successful realisation of single photon emission with a g(2)(0) of 0.21, a high polarisation degree of 0.80, a fixed polarisation axis determined by the underlying crystallography, and a GHz repetition rate with a radiative lifetime of 357 ps at 220 K in semiconductor quantum dots. The temperature insensitivity of these properties, together with the simple planar epitaxial growth method and absence of complex device geometries, demonstrates that fast single photon emission with polarisation control can be achieved in solid-state quantum dots above the Peltier temperature threshold, making this system a potential candidate for future on-chip applications in integrated systems.